2018
DOI: 10.18805/ijar.b-799
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Brucella antibodies in selected wild animals and avian species in Pakistan

Abstract: Brucellosis is a zoonotic disease which affects humans, farm animals and wildlife as well. In Pakistan, the status of human and farm animal brucellosis is documented but the information about brucellosis in wildlife is lacking. To access the seroprevalence of Brucella antibodies in avian (turkeys, peafowl, guineafowl, mallard ducks and Indian blue rock pigeon) and selected wild species (reptiles and amphibians), a total of 117 serum samples (reptile = 34, amphibian = 04, avian n = 79) were collected from Karac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 15 publications
1
18
1
Order By: Relevance
“…Data for bucks (3.4%) and for female (0.8%) goats are in contrast to earlier results of [ 29 , 38 ], who found female herds often seropositive. The present results are also opposite to results of a study conducted in Michoacan, Mexico, in small ruminants with 9% prevalence in females and 5% in males [ 39 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Data for bucks (3.4%) and for female (0.8%) goats are in contrast to earlier results of [ 29 , 38 ], who found female herds often seropositive. The present results are also opposite to results of a study conducted in Michoacan, Mexico, in small ruminants with 9% prevalence in females and 5% in males [ 39 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Human brucellosis is well reported and has been described as a professional health hazard [16][17][18]. However, knowledge on the status of infection and possible epidemiological role of non-ruminant domestic animals (equine, canine, and feline) and wildlife in brucellosis remains scarce in the country [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…This cohabitation system enhances potential transmissions from animals. A minimal number of studies [20][21][22][23][24][25] were performed in different countries to investigate whether poultry can harbor the Brucella organism (Table 1). Recently, Ali and colleges collected blood samples from 79 different avian species in Pakistan.…”
Section: Serological Evidence Of Brucellosis In Birdsmentioning
confidence: 99%
“…Recently, Ali and colleges collected blood samples from 79 different avian species in Pakistan. The use of the Rose Bengal test (RBT) showed that two samples from a peafowl (Pavo cristatus) and an Indian blue rock pigeon (Columba livia) were positive [20]. A serological survey of traditionally managed 556 local chickens, 84 guinea fowl, 50 ducks, and 40 turkeys in Borno State, North-Eastern Nigeria using the RBT and the microtiter agglutination test (MAT) showed different degrees of seroprevalence.…”
Section: Serological Evidence Of Brucellosis In Birdsmentioning
confidence: 99%
See 1 more Smart Citation